Microstructure and Properties of Spot Welded Joints of Hot-Stamped Ultra-High Strength Steel Used for Automotive Body Structures - Zhixia Qiao; Huijun Li; Lianjin Li; Xiaoyu Ran; Liwen Feng (Metals, 2019)
Hot-stamped ultra-high strength steels have been widely used in automobile structural parts. Considering the high splash tendency in resistance spot welding due to their extremely high hardness, in this work, microstructural characteristics and mechanical performance of the resistance spot welded ultra-high strength steels are investigated. The results indicate that the interface between the nugget and heat-affected zone (HAZ) is the weakest zone where fractures initiate. In tensile shearing tests, a qualified spot welding joint failed with a button-shaped fracture. Welding defects would significantly decrease the load-carrying capacity and lead to interfacial fracture, except for a button-shaped fracture. In spot welding, it was found that a specific mid-frequency alternating current (AC) input mode, in which a 6 ms cooling cycle was inserted between every two neighboring current pulses, can avoid the splash in the spot welding of hot-stamped hardened steels.